New Teachers in Nordic Countries Ecologies of Mentoring and Induction - Olsen, Knut-Rune; Bjerkholt, Eva Merete; Heikinnen, Hannu L.T (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2020)
This research based anthology is the result of a collaboration between teacher educators, researchers and representatives of teacher organizations in Denmark, Finland, Estonia, Iceland, Norway and Sweden. Some initial results of the studies introduced in this book have been shared with the international research community in the field at conferences in Europe in 2018 and 2019. In this anthology, we present and discuss significant parts of this material, aiming at stimulating a research-oriented and evidence-based development of induction and mentoring for newly qualified teachers.